Lecture notes in numerical analysis with mathematica - Styś, Tadeusz; Styś, Krystyna (Bentham Science Publishers, Inc., 2014)
The contents of this book include chapters on floating point computer arithmetic, natural and generalized interpolating polynomials, uniform approximation, numerical integration, polynomial splines and many more. This book is intended for undergraduate and graduate students in institutes, colleges, universities and academies who want to specialize in this field. The readers will develop a solid understanding of the concepts of numerical methods and their application. The inclusion of Lagrane and Hermite approximation by polynomials, Trapezian rule, Simpsons rule, Gauss methods and Rombergs̀ met.